Pengaruh Emotional Branding dan Experiential Marketing Terhadap Loyalitas Pelanggan dan Kepuasan Pelanggan Sebagai Variabel Intervening pada Brand Skincare Avoskin (Studi Kasus Generasi Z di Kec. Lowokwaru, Kota Malang) - Alika, Lingling Ayu; Arifin, Rois; Primanto, Alfian Budi (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study aims to determine and analyze the effect of emotional branding and experiential marketing on customer loyalty and customer satisfaction as intervening variables in the Avoskin skincare brand. The population of this study is Generation Z in Lowokwaru District, Malang City aged 18-25 years and have made purchases or interacted with products by implementing emotional branding and experiential marketing strategies. While the sample in this study amounted to 90 samples. The data analysis used MRA Process Macro by Hayes 2018. The results of the study show that 1) Emotional branding has a positive and significant effect on customer satisfaction 2) Experiential marketing has a positive and significant effect on customer satisfaction 3) Emotional branding has a positive and significant effect on customer loyalty 4) Experiential marketing has a positive and significant effect on customer loyalty 5) Customer satisfaction has a positive and significant effect on customer loyalty 6) Emotional branding has a positive and significant effect on customer loyalty through customer satisfaction. 7) Experiential marketing has an effect on customer loyalty through customer satisfaction but the results are not significant. Keywords: Emotional Branding, Experiential Marketing, Customer Loyalty, Customer Satisfaction